Klaim Kebenaran Tunggal dan Silent Majority dalam Ruang Digital - Subhan, Hadi; Azizah Nur Cholifatun; Durotul Mufidah; Irfa Ilmi (Bahasa Indonesia, 2025)
The development of social media has changed the landscape of Islamic preaching, enabling the widespread and rapid spread of religious discourse. However, amidst this diversity, a single truth claim has emerged, namely the tendency of a group to consider their understanding as the only correct one while other views are considered deviant. This phenomenon is further strengthened by social media algorithms that encourage the polarization of religious discourse. On the other hand, there is a silent majority group that is not actively debating but plays a role in shaping public opinion through their consumption patterns and dissemination of information. This study uses critical discourse analysis (CDA) to examine how the claim of a single truth and the silent majority are formed in the discourse of Islamic preaching on social media, focusing on the posts of the Instagram accounts @manhaj_salaf_mulia and @nuonline_id. The results show that accounts with a single truth claim build exclusive narratives and delegitimize other groups, while accounts representing the silent majority display more inclusive and moderate discourse. This study highlights how interactions between these groups shape the dynamics of digital preaching and how religious understanding develops in the social media ecosystem.